Intercultural competence as part of professional qualifications : a training experiment with Bachelor of Engineering students - Korhonen, Kaisu (Jyväskylä studies in communication, 2002)
Yhteenveto: Kulttuurienvälinen kompetenssi ammattitaidon osatekijänä : koulutuskokeilu amk-insinööriopiskelijoiden kanssa.